Facile Photoreduction Process for ZnO/Ag Hierarchical Nanostructured Photoelectrochemical Cell Integrated with Supercapacitor. (1st January 2015) - Kwon, Jinhyeong; Cho, Hyunmin; Lee, Habeom; Hong, Sukjoon; Suh, Young D.; Moon, Hyunjin; Kim, Dongkwan; Choi, Jun-ho; Lee, Ming-Tsang; Yeo, Junyeob; Ko, Seung Hwan
Abstract : ZnO/Ag hierarchical nanostructure is fabricated by solution-based photoreduction process to demonstrate a photoelectrochimical (PEC) cell charging supercapacitor. The photoreduction process ensures rapid and simple route for employing of Ag nanoparticles onto the surface of ZnO nanorod with well-dispersed and clear crystallization structure. The fabricated ZnO/Ag hierarchical nanostructure showed improved optical and photoelectrochemical properties. Subsequently, the ZnO/Ag hierarchical nanostructure is used as photoanode for PEC cell with enhanced output photocurrent and stability. Furthermore, the PEC cell was connected to lab-made supercapacitors to turn on a light emitting diode. The photoreduction-processed ZnO/Ag hierarchical nanostructures provide a promising and simple production method for energy source in water splitting applications.